2013
DOI: 10.3892/or.2013.2304
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-138 enhances the proliferation, migration and invasion of cholangiocarcinoma cells through the upregulation of RhoC/p-ERK/MMP-2/MMP-9

Abstract: microRNAs (miRs) play an important role in tumor initiation and progression in many types of cancer, including cholangiocarcinoma (CC). miR-138 dysregulation is frequently observed in a variety of tumors. In the present study, miR-138 was found to be downregulated in CC tissues by quantitative real-time RT-PCR. Furthermore, its potential target molecule, Ras homolog gene family, member C (RhoC) protein, was found to be highly expressed in CC tissues examined by western blot analysis. Luciferase reporter assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 40 publications
5
56
1
Order By: Relevance
“…4 MiR-138 acts as a tumor suppressor in various types of cancer, including non-small cell lung cancer, 11 head and neck squamous cell carcinoma, 12 and cholangiocarcinoma. 13 MiR-138 was found to be downregulated in cholangiocarcinoma tissues. The introduction of miR-138 mimics to cholangiocarcinoma cells and may suppress proliferation, G1/S transition, migration and invasion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…4 MiR-138 acts as a tumor suppressor in various types of cancer, including non-small cell lung cancer, 11 head and neck squamous cell carcinoma, 12 and cholangiocarcinoma. 13 MiR-138 was found to be downregulated in cholangiocarcinoma tissues. The introduction of miR-138 mimics to cholangiocarcinoma cells and may suppress proliferation, G1/S transition, migration and invasion.…”
Section: Discussionmentioning
confidence: 93%
“…The introduction of miR-138 mimics to cholangiocarcinoma cells and may suppress proliferation, G1/S transition, migration and invasion. 13 Moreover, in head and neck squamous cell carcinoma, it was found that overexpressed miR-138 attenuated the downstream signaling cascade, extracellular signal-regulated kinase (1/2), leading to cancer progression and survival. 12 MiR-138 has been recognized as a potential tumor suppressor because it regulates PDK1 expression in non-small cell lung cancer cells, which are independent prognostic factors for overall survival in non-small cell lung cancer cells patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the RhoC/p-ERK/MMP-2/ MMP-9 pathway is upregulated, which causes enhanced proliferation, migration and invasion of cholangiocarcinoma cells. 64 In addition, miR-138 could target directly the Twist basic helix-loop-helix transcription factor 2 gene (TWIST2) and reduce its function, which inhibits migration and invasion in colorectal cancer. 65 Besides, miR-138 is ovarian cancer-specific, where it functions to inhibit ovarian cancer cell growth by blocking the proliferating cell nuclear antigen (PCNA) and Bcell lymphoma-2 (Bcl ÂĄ 2) pathway.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…Although little is known about the role of miRNAs in regulating cholangiocyte proliferation and function [215], several studies implicated specific miRNAs in the pathogenesis of cholangiocarcinoma. For example, the overexpression of miR-31 in cholangiocarcinoma cells altered RAS/MAPK signaling [216], and miR-138 can regulate cholangiocarcinoma proliferation, cell-cycle control, and migration, possibly by directly targeting RhoC [217]. miR-506 regulates the expression of anion exchanger 2 (AE2), and the suppression of miR-506 leads to improved AE2 function in primary biliary cirrhosis cholangiocytes [82].…”
Section: Liver Tissue Engineeringmentioning
confidence: 99%